Cell cycle-specific phosphorylation of p53 protein in A549 cells exposed to cisplatin and standardized air pollutants - Niechoda, Agata; Milewska, Katarzyna; Roslan, Joanna; Ejsmont, Karolina; Holownia, Adam (Frontiers in Physiology, 2023)
Exposure to particulate matter is associated with DNA damage and the risk of lung cancer. Protein p53 is activated by multi-site phosphorylation in the early stages of DNA damage and affects cell outcome. Our study aimed to assess the effect of (100 µg/mL - 1 /24 hours) standardized air pollutants: carbon black (CB), urban dust (UD), and nanoparticle carbon black (NPCB) on cell cycle, DNA damage and 53 phosphorylation at Ser 9, Ser 20, Ser 46 and Ser 392 in proliferating and quiescent A549 cells and in cells that survived cisplatin (CisPT) exposure. Phosphorylated p53 was quantified in cell subpopulations by flow cytometry using specific fluorochrome-tagged monoclonal antibodies and analysis of bivariate fluorescence distribution scatterplots. CisPT, UD and NPCB increased site-specific p53 phosphorylation producing unique patterns. NPCB activated all sites irrespectively on the cell cycle, while the UD was more selective. p53 Ser 9-P and p53 Ser 20-P positively correlated with the numbers of CisPT-treated cells at G0/G1, and NPCB and NPCB+CisPT produced a similar effect. A positive correlation and integrated response were also found between Ser 20-P and Ser 392-P in resting A549 cells treated with NPCB and CisPT but not UD. Interdependence between the expression of p53 phosphorylated at Ser 20, and Ser 392 and cell cycle arrest show that posttranslational alterations are related to functional activation. Our data suggest that p53 protein phosphorylation in response to specific DNA damage is driven by multiple independent and integrated pathways to produce functional activation critical in cancer prevention and treatment.